3D automotive modeling : an insider's guide to 3D car modeling and design for games and film - Gahan, Andrew (Focal Press, 2011)
Master techniques from top automotive designers and world-class game developers with this insider's guide to designing and modeling 3D vehicles. With techniques demonstrated in 3ds Max, Maya, XSI, and Photoshop, 3D Automotive Modeling starts with a fantastic series of hot concept designs and continues by offering a full hands-on modeling tutorial for each. Some of the very best designers and modelers from across the globe take you through their processes step-by-step, giving you the tips, tricks, and short-cuts that true professionals use. 3D Automotive Modeling features tutorials from Honda, Toyota, and Mercedes-Benz designers, as well as modelers from Sony Computer Entertainment, Lucas Arts, and Simbin-artists who have worked on some of the biggest games in the industry, including the MotorStorm series